What God Cannot Do: Divine Power, the Gratuity of Grace, and Henri De Lubac. (11th March 2020) - Lombardo, Nicholas E.
Abstract: When Pius XII promulgated his encyclical Humani generis in 1950, it was widely read as censuring Henri de Lubac's views on human nature and the desire for God. In recent years, as controversies about nature and grace have revived, this reading of Humani generis has been widely assumed by supporters and critics of de Lubac alike. Henri de Lubac, however, always insisted that the encyclical did not touch his position. This article will argue that, whatever the objectives of the encyclical's drafters, he was correct. It will make its case by turning to an issue neglected in contemporary debates about nature and grace: divine power. It will first trace the history of Christian reflection on divine power, a story whose twists and turns have only recently been uncovered by medieval historians, and then argue that, with this history in view, interpreting the crucial line in Humani generis as excluding de Lubac's position becomes untenable. Finally, this article will discuss the implications of this conclusion for contemporary accounts of human nature, the desire for God, and the gratuity of grace.